Padronização do 152Eu pelo método pico-soma precedido da dedução de expressões teóricas para as taxas de contagem - Filho, Alfredo Lopes Ferreira (2018)
The objective of this work is the development, in the field of radionuclide metrology, of a primary measurement technique of the quantity activity per mass unit, by a theoretical-experimental approach of the Sum-Peak Coincidence Method which allows direct standardization of the complex decay radionuclide 152Eu, in which the deexcitation cascade nucleus occurs simultaneously with the cascade de-excitation of the atomic layer. The Sum-peak Coincidence Method, an absolute measurement technique that uses coincidence counting and γ-ray spectrometry, was applied to activity standardization of 152Eu sources. The decay branch used was that of 152Sm, as it is almost entirely electron capture and exhibits X-rays with a high probability of coincidence with the 121.8 keV gamma rays, as evidenced by the matrix technique used for complex decay schemes, a method for deriving counting rate equations describing coincidence summing of gamma and X-rays. The result was compared with the calibration performed by ionization chamber traceable to BIPM. The results presented uncertainty values of 0.50 % (k = 1).